0998 Health Care Utilization of Pediatric Sleep Disorders in Cerner Health Facts Database. (27th May 2020) - Al-Shawwa, B; Glynn, E; Hoffman, M; Ehsan, Z; Ingram, D
Abstract: Introduction: This study was aimed to identify health care utilization of sleep disorders in pediatrics and adults by using Cerner health facts database. Methods: Health facts database has unidentified health records from all the participating facilities that have Cerner as their electronic medical records software. There are 68.7 million patients in the data warehouse with about 506.9 million encounters in about 100 healthcare systems. Sleep disorders are mostly seen in outpatient settings and therefore this study included outpatient records between the years 2010 to 2017. Results: There were 20.5 million patients with total of 127.4 million outpatient encounters. In pediatric patients (ages 0-18 years), healthcare utilization of major sleep diagnoses per 100, 000 encounters showed sleep related breathing disorders are the most commonly seen followed by parasomnia, insomnia, sleep movement disorders, hypersomnolence then circadian rhythm disorders (820.1, 258.1, 181.6, 68.3, 48.1 and 16.2 per 100, 000 encounters). However, for adult patients the ranking was: sleep related breathing disorders, insomnia, sleep related movement disorders, hypersomnolence, parasomnia then circadian rhythm disorders (1352.6, 511.6, 166.3, 79.1, 25.7 and 4.2 per 100, 000 encounters). Further analysis for the age groups showed bimodal pattern for sleep related breathing disorders and sleep movement disorders with the highest utilization were between the ages of 2-11 year and 40-60 years. Adolescents (age 12-18 years) showed increase utilization in the areas of circadian rhythm disorders. Conclusion: Patients with sleep disorders have relatively low health care utilization despite high prevalence of these sleep disorders in the general population. This may highlight underrecognized sleep problem or decreased access to health care. In addition, this study highlights the effect of age on different sleep disorders which may have an impact on allocating resources. Support: None